Tea polyphenols for the prevention of UVB‐induced skin cancer. Issue 1 (20th November 2017) - Sharma, Pooja; Montes de Oca, Mary K.; Alkeswani, Amena R.; McClees, Sarah F.; Das, Tanushree; Elmets, Craig A.; Afaq, Farrukh
Summary: Skin cancer is the most common type of cancer with increasing incidence rate and public health burden. Solar ultraviolet (UV) radiation causes an array of damaging cellular and molecular events that eventually lead to the development of skin cancer. Despite increased awareness about sun protection, the exposure rate remains high with less than 15% of men and 30% of women using sunscreen on a regular basis. Therefore, there is an imperative need for the development of novel preventive approaches. Skin cancer chemoprevention using phytochemicals either as dietary supplements or by topical applications has gained considerable attention due to their low toxicity, availability, and anticarcinogenic properties. Tea, the second most commonly consumed beverage in the world, is a rich source of promising phytochemicals known as polyphenols. In this review, we discuss the findings of various in vitro, in vivo and human studies signifying the chemopreventive effects of tea polyphenols against UVB‐induced skin cancer. This is accomplished by exploring the role of tea polyphenols in DNA repair, inflammation, oxidative stress, signaling pathways, and epigenetics. Finally, this review discusses a variety of innovative delivery methods that enhance the photochemopreventive effects of tea polyphenols against skin cancer.